Menuju Penyederhanaan Partai Politik yang Proporsional di Indonesia: Tinjauan Komparatif dan Alternatif Desain - Muhammad Iqbal Kholidin; Mochamad Adli; Diva Nugraha (Jurnal Silatene Sosial Humaniora, 2026)
The parliamentary threshold plays a crucial role in shaping Indonesia’s electoral system by determining the minimum percentage of votes required for political parties to obtain parliamentary seats. While designed to simplify the multiparty system and enhance governmental effectiveness, its implementation has sparked debates on political representation and democratic fairness. This study analyzes the impact of Indonesia’s parliamentary threshold by comparing it with Uruguay’s more inclusive proportional representation system. Using a qualitative approach through document analysis and comparative case studies, the findings indicate that a high threshold can reduce party fragmentation but also risks excluding votes from smaller parties. The study recommends alternative measures such as lowering the threshold and adjusting electoral district sizes to balance stability and representation. Uruguay’s experience demonstrates that political inclusivity does not necessarily undermine governmental stability, underscoring the need for Indonesia to reconsider its threshold policy to achieve proportionality and political equilibrium